A Tabletop UV Microscope. - Minkel, J.R (IEEE spectrum)
Researchers from the Colorado State University and Lawrence Berkeley National Laboratory's Center for X-ray Optics have developed a high-resolution ultraviolet microscope that fits on a tabletop. Researchers were able to get enough resolving power from a relatively small setup by providing a better alignment of the titanium-sapphire laser, the silver-cadmium pellet, and the diffraction plates. These tabletop UV lasers have the potential to serve as candidate inspection systems for future lithographic masks